2019
DOI: 10.21852/sem.2019.1.09
|View full text |Cite
|
Sign up to set email alerts
|

Poczucie godności osobistej a struktura wartości polskich studentek

Abstract: The issue of dignity seems to be returning in the scientific reflection in the context of cultural and civilization changes. In recent decades they relate to a large extent the role and tasks of the modern woman. The problem o f this w o rk concentrate on the q u estion about the relationship between the sense of personal dignity and the preferences of young women's values/goals.197 students aged 19-24 were examined and the following tools were used: the Self-esteem of Self-Dignity (KPWG), Portrait Questionnai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Brudek's (2017) research indicates that there are differences in the level of SSD depending on the level of sexual satisfaction in people's late adulthood. Salwa and Kulik (2019) found that the value preference of women with a high sense of personal dignity is significantly different from that of women with a low sense of personal dignity. Research with female students showed that young women with a high SSD are developmentally oriented, while their colleagues with lower SSD prefer adjustment (Salwa & Kulik, 2019).…”
mentioning
confidence: 86%
See 1 more Smart Citation
“…Brudek's (2017) research indicates that there are differences in the level of SSD depending on the level of sexual satisfaction in people's late adulthood. Salwa and Kulik (2019) found that the value preference of women with a high sense of personal dignity is significantly different from that of women with a low sense of personal dignity. Research with female students showed that young women with a high SSD are developmentally oriented, while their colleagues with lower SSD prefer adjustment (Salwa & Kulik, 2019).…”
mentioning
confidence: 86%
“…Salwa and Kulik (2019) found that the value preference of women with a high sense of personal dignity is significantly different from that of women with a low sense of personal dignity. Research with female students showed that young women with a high SSD are developmentally oriented, while their colleagues with lower SSD prefer adjustment (Salwa & Kulik, 2019). In addition, women with disability have a higher sense of SSD than men with disabilities in the scope of the dimension of the disability loss and the total result of the Questionnaire of Sense of Self-Dignity (QSSD-3) (Grudziewska & Mikołajczyk, 2020).…”
mentioning
confidence: 86%